A5_7 warming up your hands - Haywood, Jacob; Topping, Niamh; Butcher, William; Sisodia, Nikhil (Physics Special Topics, 2021)
This paper explores how effective rubbing your hands together is to generate heat, and extrapolates to find the upper limits of what can be done whilst neglecting heat loss to the surroundings. We find that for a small applied force, the temperature gain from the act of rubbing one hand over the other is T = 9.39 × 10−4K, whereas for the strongest push force for a human arm the temperature gain is δT = 0.085K. For the smaller temperature gain, it is shown to take 5.79 hours to form first degree burns, whereas for the high temperature gain it can take as little as 3.8 minutes.